Long-term effectiveness of a multicomponent frailty management program in Singapore: One-year preliminary findings of a cluster-randomised controlled trial - Tianma Xu; Rhin Tok; Yan Ying Tay; Shi Ting Lai; Grace Hui Ling Tan (Archives of Gerontology and Geriatrics Plus)
The prevalence of frailty is increasing with the rapidly ageing population in Singapore. A 12-week multicomponent frailty management program, “Say No to Frailty” (SNTF) showed its feasibility and demonstrated positive outcomes. This study aimed to evaluate the long-term clinical effectiveness of the SNTF program on various health outcomes in community-dwelling older adults with pre-frailty and frailty in Singapore. As part of the larger cluster-randomised controlled trial (c-RCT), participants from three intervention groups were included. Two groups were led by Allied Healthcare Professionals (AHPs) (n = 19) and one group was led by a non-AHP (n = 8). Assessments on frailty status (Clinical Frailty Scale), physical functions (Short Physical Performance Battery and hand grip strength), self-efficacy (Falls Efficacy Scale – International), participation (Life-Space Assessment and Goal Attainment Scale), and quality of life (EQ-5D-5 L) were conducted at baseline, 3 months, 6 months and 12 months. Data were analysed using mixed ANOVA to compare the changes between and within groups. Monthly fall data were collected and analysed. Statistically significant improvements in all health outcomes at 12-month follow-up were observed in all intervention groups. There was no significant difference found in most outcome measures between groups across all time points. Fall reduction post-intervention was observed. SNTF demonstrated potential long-term effectiveness in improving frailty status, physical functions, self-efficacy, community participation, quality of life and fall reduction in the community-dwelling older adults with pre-frailty and frailty in Singapore, regardless of the training background of the program facilitators.